2011
DOI: 10.1007/s00127-011-0399-z
|View full text |Cite
|
Sign up to set email alerts
|

Labels used by young people to describe mental disorders: which ones predict effective help-seeking choices?

Abstract: Labelling a disorder accurately does predict a preference for recommended sources of help and a belief in the helpfulness of recommended treatments. Importantly, it is also apparent that some commonly used lay labels cannot do this and indeed may limit appropriate help-seeking and treatment acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
42
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 35 publications
8
42
3
1
Order By: Relevance
“…) and support during a mental health crisis (Wright et al, 2012;Yap et al, 2015). Our data support this hypothesis because lay people who correctly identified the nature of the problem had higher intentions to recommend help to mental health professionals.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…) and support during a mental health crisis (Wright et al, 2012;Yap et al, 2015). Our data support this hypothesis because lay people who correctly identified the nature of the problem had higher intentions to recommend help to mental health professionals.…”
supporting
confidence: 71%
“…For hypotheses relating to recognition, labelling, and effect of vignette, non-parametric tests were used because the dependent variable of accuracy was negatively skewed and dependent variable labelling correctness was categorical. In line with previous research (Wright et al, 2012), we controlled for age and gender, which are known predictors of help-seeking. Those who selected the label psychosis/schizophrenia spectrum disorder (coded 1 = correct) were compared with those who selected other labels (coded 2 = incorrect).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, it would seem that there is still progress to be made in improving access to information about symptoms, treatments and others' experiences of depression, as well as information about ongoing research. Being able to identify and label the problem has been shown to predict effective help-seeking behaviours (Wright et al 2012), and it is important that the symptoms of depression are recognised and that appropriate supports are identified at an early stage. Wilson et al (2007) found that intention to seek help decreased as depressive symptoms increased, in a sample of children and adolescents.…”
Section: Mental Health Literacy and The Mediamentioning
confidence: 99%